How Instructors’ TPACK Developed During Emergency Remote Teaching: Evidence From Instructors in Faculties of Education - Çakıroğlu, Ünal; Aydın, Merve; Bahadır Kurtoğlu, Yılmaz; Cebeci, Ümit (International Review of Research in Open and Distributed Learning, 2023)
Higher education instructors tried to find best teaching ways during the pandemic. Instructors who were faced with emergency situations used various technologies to deliver their courses. In this study, an online survey was used to ask instructors about their experiences regarding their development of technological pedagogical content knowledge (TPACK) during emergency remote teaching (ERT); 231 responses were received from instructors from faculties of education. The survey was a five-point Likert-type scale include the dimensions of pedagogical knowledge, pedagogical knowledge, technological knowledge, technological content knowledge, pedagogical content knowledge, technological pedagogical knowledge, and technological pedagogical content knowledge. Instructors rated their own non-technological knowledge (pedagogical knowledge, content knowledge, and pedagogical content knowledge) relatively higher than their knowledge including technology (technological knowledge, technological pedagogical knowledge, and technological content knowledge). The findings indicate that instructors had a consistently high level of perceived knowledge in all TPACK dimensions. Regarding developments in instructors’ TPACK, several suggestions were made, including novel technologies and pedagogies specialized for ERT.